Вопросы социального партнерства педагогического вуза и учреждений образования на современном этапе развития общества - Кифик, Н.Ю. (My University, 2016)
This problem is considered from the point of interaction between Kostanay state pedagogical institute and educational institutions on various dimensions, including joint events, development of joint curricula and others.